Development and validation of potential molecular subtypes and signatures of ocular sarcoidosis based on autophagy-related gene analysis - Wu Zixuan; Long Xi; Tan Kang; Yao Xiaolei; Peng Qinghua (Open Medicine)
Sarcoidosis is characterized by the proliferation of noncaseating granulomas and presents as a complex chronic inflammatory disease. Autophagy plays a crucial role in the initiation, progression, and treatment resistance of various cancers. Despite the recognized importance of autophagy, the involvement of autophagy-related genes (ARGs) in the pathophysiology of ocular sarcoidosis (OS) remains largely unexplored.